Get out of bed! - Munsch, Robert (New York : Scholastic Inc, 1998)
When Amy won't get out of bed, her parents don't know what to do. Amy's brother comes up with a wacky solution that gets Amy to school on time--but will her school ever be the same?
Keywords: Children stories; Sleeping--Fiction